Decrease in ionized and total magnesium blood concentrations in endurance athletes following an exercise bout restores within hours-potential consequences for monitoring and supplementation - Terink, R.; Balvers, M. G. J.; Hopman, M. T.; Witkamp, R. F.; Mensink, M.; Klein Gunnewiek, J. M. T. (International Journal of Sport Nutrition and Exercise Metabolism, 2017)
Magnesium is essential for optimal sport performance, generating an interest to monitor its status in athletes. However, before measuring magnesium status in blood could become routine, more insight into its diurnal fluctuations and effects of exercise itself is necessary. Therefore, we measured the effect of an acute bout of exercise on ionized (iMg) and total plasma magnesium (tMg) in blood obtained from 18 healthy well-trained endurance athletes (age, 31.1 ± 8.1 yr.; VO2max, 50.9 ± 7.5 ml/kg/min) at multiple time points, and compared this with a resting situation. At both days, 7 blood samples were taken at set time points (8:30 fasted, 11:00, 12:30, 13:30, 15:00, 16:00, 18:30). The control day was included to correct for a putative diurnal fluctuation of magnesium. During the exercise day, athletes performed a 90 min bicycle ergometer test (70% VO2max) between 11:00 and 12:30. Whole blood samples were analyzed for iMg and plasma for tMg concentrations. Both concentrations decreased significantly after exercise (0.52 ± 0.04-0.45 ± 0.03 mmol/L and 0.81 ± 0.07-0.73 ± 0.06 mmol/L, respectively, p < .001) while no significant decline was observed during that time-interval on control days. Both, iMg and tMg, returned to baseline, on average, 2.5 hr after exercise. These findings suggest that timing of blood sampling to analyze Mg status is important. Additional research is needed to establish the recovery time after different types of exercise to come to a general advice regarding the timing of magnesium status assessment in practice.